RNA N1-methyladenosine regulator-mediated methylation modification patterns and heterogeneous signatures in glioma - Mao, Meng; Chu, Qinjun; Lou, Yongli; Lv, Peipei; Wang, Lin-jian (Frontiers in Immunology, 2022)
N1-methyladenosine (m1A) is ubiquitous in eukaryotic RNA and regulates mRNA translation. However, little is known about its regulatory role in glioma. Here, we identified 4 m1A modification-related patterns based on m1A regulators in the TCGA and CGGA cohorts. The differences in survival prognosis between different clusters were striking. In addition, stemness, genomic heterogeneity, tumor microenvironment (TME), and immune cell infiltration were also significantly different between the poor and best prognostic clusters. To reveal the underlying mechanism, differentially expressed genes (DEGs) between the poor and best prognostic clusters were identified, and then were integrated for weighted correlation network analysis (WGCNA). After Univariate Cox-LASSO-Multivariate Cox analyses, DEGs PLEK2 and ABCC3 were screened as the risk-hub genes and were selected to construct an m1A-related signature. Moreover, ABCC3 promoted glioma proliferation and was associated with temozolomide (TMZ) resistance. Overall, our study provided new insights into the function and potential therapeutic role of m1A in glioma.